When and How Is It Possible to Stop Therapy in Patients with Lupus Nephritis: A Narrative Review. Issue 12 (December 2021) - Moroni, Gabriella; Frontini, Giulia; Ponticelli, Claudio
Abstract : Glucocorticoids and other immunosuppressants still represent the cornerstone drugs for the management of SLE and lupus nephritis. The refined use of these drugs over the years has allowed us to obtain stable disease remission and improvement of long-term kidney and patient survival. Nevertheless, a prolonged use of immunosuppressive agents may be accompanied by severe and even life-threatening side effects. Theoretically, a transient or even definitive withdrawal of immunosuppression could be useful to prevent iatrogenic morbidities. For many years, however, the risk of SLE reactivation has held clinicians back from trying to interrupt therapy. In this review, we report the results of the attempts to interrupt glucocorticoids and other immunosuppressive agents in lupus nephritis and in SLE. The available data suggest that therapy withdrawal is feasible at least in patients enjoying a complete clinical remission after a prolonged therapy. A slow and gradual reduction of treatment under medical surveillance is needed to prevent flares of activity. After therapy withdrawal, around one-quarter of patients may have kidney or systemic flares. However, most flares may respond to therapy if rapidly diagnosed. The other patients can enter stable remission for even 20 years or more. The use of antimalarials can help in maintaining the remission after the withdrawal of the immunosuppressive therapy. A repeated kidney biopsy could be of help in deciding to stop therapy, but given the few available data, it cannot be considered essential.